Pseudo-Collaboration as a Method to Perform Selective Algorithmic Mediation in Collaborative IR Systems - González-Ibáñez, Roberto; Shah, Chirag; White, Ryen W. (75th Annual Meeting of the American Society for Information Science and Technology (ASIS&T 2012) Baltimore, Maryland, U.S.A., 2012)
Traditional recommendation systems suggest results based on data collected from users’ actions. Many of the newer information retrieval (IR) systems incorporate social search or collective search signals as an extension to standard term-based retrieval algorithms. Systems based on social or collaborative search methods, however, do not consider when, how, and to what extent such support could help or hurt their users’ search performance. In this poster we propose a novel approach of selective algorithmic mediation capable of identifying when a user should be aided by a collaborator and to what extent such help could enhance search success. We demonstrate the applicability and benefits of our approach through simulations using a pseudo-collaboration method on the log data of individual users and pairs of users gathered during a laboratory study with 131 participants. The results show that our approach can improve the search performance of both individual searchers and others collaborating intentionally by identifying and recommending regions in search processes with best chance of improvements, thus increasing the likelihood that users find more useful information with less effort.